1991
DOI: 10.1073/pnas.88.23.10726
|View full text |Cite
|
Sign up to set email alerts
|

A broadly neutralizing monoclonal antibody that recognizes the V3 region of human immunodeficiency virus type 1 glycoprotein gp120.

Abstract: Previous studies have demonstrated that the principal neutralizing determinant of human iunodeficiency virus type 1 (HIV-1) is located in the V3 loop of glycoprotein gpl20. Antibodies prepared against this region using gp120 or peptides as immunogens have been predonminantly HIV-1-isolate-specific. In the present studies, murine monoclonal antibodies (mAbs) were prepared against the HIV-1MN strain. One mAb, designated NM-01, was selected for its ability to neutralize both the MN and TUB strains. Neutralization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…Specifically, we found that Th epitopes are clustered within hot spots on one exposed face of HIV gp120 (14,15). Many of these T cell epitopes overlap with known Ab binding domains (16,17). Studies of influenza and parainfluenza viral membrane proteins have similarly shown that immunodominant Th cell epitopes can be localized to exposed protein surfaces (18 -21).…”
mentioning
confidence: 92%
“…Specifically, we found that Th epitopes are clustered within hot spots on one exposed face of HIV gp120 (14,15). Many of these T cell epitopes overlap with known Ab binding domains (16,17). Studies of influenza and parainfluenza viral membrane proteins have similarly shown that immunodominant Th cell epitopes can be localized to exposed protein surfaces (18 -21).…”
mentioning
confidence: 92%
“…Historically, it has been difficult to induce neutralizing antibody responses against diverse primary HIV type 1 (HIV-1) strains by utilizing monomeric HIV Env (i.e., gp120) glycoprotein. Furthermore, it has been shown by several groups that the antibody responses induced by gp120 are directed primarily against the V3 loop and other linear epitopes (22,34,43,44,70,81,82,102,109,110,117) and that limited responses are directed towards the conserved conformational epitopes (9,41,75,88,95,107). Due to the high degree of variability in gp120, these nonconformational anti-gp120-specific antibodies were found to be predominantly subtype specific and, to some extent, isolate specific.…”
mentioning
confidence: 99%
“…Interaction of R-95288 with the V3 loop seems to be an electrostatic attraction because all anti-V3 MAbs which competed with R-95288 recognized a basic amino acid sequence, RKSIR, rather than GPGRAF as the principal neutralizing domain for antibodies in gp120 ofHIV-1 IIIB (Javaherian et al, 1990;Ohno et al, 1991). Recent reports suggest that heparin binds to the consensus amino acid sequence BBXB, BBXXB orBBXXXB (B, basic amino acid; X, non-basic amino acid ;Cardin & Weintraub, 1989) and interacts with the RKSIR amino acid sequence of V3 peptide (Javaherian et al, 1994).…”
Section: Discussionmentioning
confidence: 99%